Marine drugs for cancer: surfacing biotechnological innovations from the oceans - Jimenez, Paula Christine (2019)
This review will discuss the contributions of marine natural molecules, a source only recently found to have pharmaceutical prospects, to the development of anticancer drugs. Of the seven clinically utilized compounds with a marine origin, four are used for the treatment of cancer. The development of these drugs has afforded valuable knowledge and crucial insights to meet the most common challenges in this endeavor, such as toxicity and supply. In this context, the development of these compounds will be discussed herein to illustrate, with successful examples provided by cytarabine, trabectedin, eribulin and brentuximab vedotin, the steps involved in this process as well as the scientific advances and technological innovation potential associated with developing a new drug from marine resources.